(untitled) (Ozone Therapy Global Journal, 2021)
Context: The ovarian cyst is a membranous pocket that is usually filled with a solid or liquid substance. It may cause different symptoms such´s as colic pain of different intensity, as well as alterations in the menstrual cycle. Current allopathic treatments include hormones and/or surgical process with different techniques. Requiring the search for new therapeutic alternatives. Aims: The present report how the effect of vaginal and rectal ozone application in a case of ovarian cyst. Methodology: Female of 43 years old, with colic pain in the left iliac fossa with a diagnosis of ovarian cyst, with fluid content. He signed an informed consent to receive ozone treatment. The ovary and cyst were evaluated by ultrasound before and after treatment. The analgesic efficacy was evaluated by the Visual Analogue Scale (VAS), taking VAS 8-9 from the initial consultation as a reference. VAS and patient satisfaction was evaluated at the beginning, at the 3rd week and at the end of the treatment. Ozone was administered vaginally 100 mL at 14 µg/mL 4 sessions, one per week; rectal ozone 60-300 mL 14 µg/mL to 24 µg/mL, 20 sessions, five per week. Results: The cyst measured 35x33x29 mm at the beginning and disappeared 18 days after the treatment ended. After three weeks with ozone therapy. The VAS scale for pain was referred as 0 (cero), patient satisfaction was excellent at the end of treatment Discussion: Ozone and its property of oxidation, analgesic and immunomodulatory properties of ozone produced a dehydrating and anti-inflammatory effect on the ovarian cyst, reducing it until its elimination, which decreased pain and regulated the patient´s menstrual cycle.